Dealing with Unwanted Donations: A Content Analysis of Small Academic Canadian Library Webpages - Cardozo, Paula (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2022)
While archives and special collections continue to welcome unique and valuable resources, small academic libraries can struggle with how to manage donation offers intended for their main collections. There is a need to be selective considering falling print circulation, workload pressures on library personnel, and space restrictions. Additionally, limited collections funds needed for more current and higher-demand resources can be strained by the higher processing costs of donated materials. These pressures are compounded by prospective donors seeking a home for items they no longer want, a perception that small academic libraries need all donations, and a lack of understanding about the qualifications and expertise of academic library workers. Clearly communicated and regularly reviewed guidelines can help discourage unwanted donations in ways that lessen alienating our patrons. This article provides a content analysis of donations webpages from small academic libraries in Canada to identify trends and provide support for libraries reviewing their own policies and procedures in an effort to manage donor expectations.